SINTESIS NANOPARTIKEL ZnO MENGGUNAKAN EKSTRAK DAUN MANGGA (Mangifera sp.) DAN STUDI APLIKASINYA SEBAGAI FOTODEGRADASI CONGO RED - Hasiah; Demi Dama Yanti; Bambang Ari Wahjoedi (ALOTROP, 2025)
Zinc oxide (ZnO) is a widely studied semiconductor material due to its broad range of applications. ZnO is known for its stability and can be synthesized using various methods. One of the approaches employed in this study is the co-precipitation method with a green synthesis approach. The green synthesis principle applied in this research involves minimizing the use of synthetic chemicals by substituting them with natural materials. Mango leaves (Mangifera sp.), which are readily available in the environment, contain secondary metabolites which can act as the capping agents in synthesis ZnO nanoparticle. The role of the capping agent is to limit particle interactions, thereby reducing agglomeration. ZnO synthesis was carried out at a low temperature by mixing Zn²⁺ precursor, NaOH, and mangifera sp. leaf extract, followed by stirring. The heating process was conducted at 130°C for 4 hours. The synthesized material was characterized using X-ray diffraction (XRD), UV-DRS, and scanning electron microscopy (SEM). The characterization results confirmed that the ZnO sample exhibited a hexagonal wurtzite crystal structure, a nanoflower morphology, and a band gap energy of 3.26 eV. Keywords: ZnO; nanoparticles; photocatalyst; congo red; co-precipitation.